Conference Review: 7th Experimental Archaeology Conference, Cardiff 2013 - Heather Hopkins (EXARC, 2013)
The 7th Experimental Archaeology Conference was held on 12-13th January 2013. This annual event, first held in 2006, has steadily increased in size. This year it was hosted jointly by the School of History, Archaeology and Religion at Cardiff University and St Fagan’s Open-Air Museum, near Cardiff. Seventy-five delegates originally booked to attend, but one hundred actually attended each day, a logistical challenge accommodated by the organisers that reflects the continued success and growing popularity of the conference. The conference consisted of two days of presentations, the first ending with poster presentations of diverse subjects that complemented the papers presented. A writer from Nature attended the first day.